Assessing Oral Language When Screening Multilingual Children for Learning Disabilities in Reading. (January 2023) - Goodrich, J. Marc; Fitton, Lisa; Chan, Jessica; Davis, C. Jamie
Multilingual children represent a rapidly growing population of students in U.S. schools. However, identification of language and learning disabilities for students from different linguistic backgrounds is complex, leading to frequent misidentification of multilingual learners for special education. This article provides guidance on how special education teachers, speech-language pathologists, and other practitioners (e.g., school psychologists) can utilize each other's expertise to accurately assess language and literacy skills of multilingual learners. Five key lessons learned from research on identification of language disorders are presented, along with discussion of why these are important when screening multilingual children for learning disabilities in reading. Specifically, there is a focus on considering children's language background, regardless of English learner status, the importance of language ability for reading achievement, common pitfalls in using standardized assessments with multilingual learners, and linguistically sensitive assessment and scoring practices to be used with multilingual students.